Acne – therapeutic challenges to the cooperation between a dermatologist and a cosmetologist - Adamski, Zygmunt; Gornowicz-Porowska, Justyna; Sobkowska, Daria; Kaszuba, Klaudyna; Czajkowski, Rafał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Acne vulgaris is one of the most common skin diseases in adolescence, causing a significant negative impact on the quality of life of young people who – in a large percentage of cases – do not accept their appearance. The complex pathogenesis of this disease requires appropriate preventive and curative treatment from both a dermatologist and a cosmetologist. The aim of the study was to discuss the methods currently used by dermatologists in local therapy for mild and intermediate forms of acne vulgaris, and to provide an overview of possible preventive and caring activities in the cosmetologist’s office. Possible directions of cooperation between the dermatologist and the cosmetologist in the prevention of acne relapse and treatment of possible acne complications were also discussed.